Outcome and Characteristics of Community Acquired Pneumonia Patients: A Single Centre Study - Muhammad Umar, Sher Ali Khan, Muhammad Salman Khan, Bilal Ahmed, Ihtesham Ullah Khan, Azhar Ud Din, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Community-acquired pneumonia is the most common form of pneumonia and is a major contributor to both morbidity and mortality globally. Objective: To assess the outcome and characteristics of Community Acquired Pneumonia patients Methodology: The current study was cross sectional study carried out at the pulmonology department, Lady Reading Hospital, Peshawar from January 2023 to June 2023. The demographic information, co-morbid illnesses, smoking history, CURB 65 score, and chest X-ray results of each patient were carefully recorded. The data was analyzed by using SPP-24. Results: A total of 180 patients were enrolled in this study. There were 108 (60%) male participants whereas 72 (40%) were female participants. Based on CURB 65 score, CURB 65 score 2, CURB 65 score 3 and CURB 65 score 4 was observed in 36 (20%), 33 (18.33%) and 12 (6.67%) patients respectively. Based on laboratory findings, >11000 WBCs were observed in 144 (80%) patients while <150,000 platelets count were observed in 36 (20%) patients. The overall mortality rate in our study was 27 (15%). Conclusion: Our study concludes that the mortality rate associated with community acquired pneumonia was high. The major complications associated with the community acquired pneumonia were parapneumonic effusion and empyema in our study. Keywords: Characteristics; Outcome; Community Acquired Pneumonia